2013
DOI: 10.1128/genomea.00132-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Vibrio parahaemolyticus SNUVpS-1 Isolated from Korean Seafood

Abstract: Vibrio parahaemolyticus is the leading cause of food-borne diseases, and several pathogenic strains cause global gastroenteritis outbreaks. Here, we report a draft genome sequence of V. parahaemolyticus SNUVpS-1, which was isolated from seafood in a fishery market in the Republic of Korea and contained TL, toxR, and toxRSold genes. The current draft genome sequence will contribute to the effort to monitor the spread of V. parahaemolyticus seafood isolates and clinical isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Unlike V. cholerae , for which the genomes of well over 100 strains have been sequenced over the past 13 years, only a few V. parahaemolyticus strains have been completely sequenced and/or annotated to date (Table 1 ) (Boyd et al, 2008 ; Chen et al, 2011 ; Gonzalez-Escalona et al, 2011 ; Jensen et al, 2013 ; Jun et al, 2013 ; Liu and Chen, 2013 ). Nevertheless, since the first strain, RIMD 2210633, was sequenced (Makino et al, 2003 ), several comparative studies have identified new genomic islands (GIs).…”
Section: Comparative Genomics: Pathogenicity Islands and The Dynamic mentioning
confidence: 99%
“…Unlike V. cholerae , for which the genomes of well over 100 strains have been sequenced over the past 13 years, only a few V. parahaemolyticus strains have been completely sequenced and/or annotated to date (Table 1 ) (Boyd et al, 2008 ; Chen et al, 2011 ; Gonzalez-Escalona et al, 2011 ; Jensen et al, 2013 ; Jun et al, 2013 ; Liu and Chen, 2013 ). Nevertheless, since the first strain, RIMD 2210633, was sequenced (Makino et al, 2003 ), several comparative studies have identified new genomic islands (GIs).…”
Section: Comparative Genomics: Pathogenicity Islands and The Dynamic mentioning
confidence: 99%
“…parahaemolyticus in the NCBI database (Supplementary Table 1) (Jun et al, 2013, Gomez-gil et al, 2014, Gomez-Jimenez et al, 2014, Kondo et al, 2014, Yang et al, 2014, Castillo et al, 2015, Kondo et al, 2015. All newly sequenced isolates exhibited more than 95% pairwise average nucleotide identity (ANI) to V. parahaemolyticus ATCC 17802 (Supplementary Figure 1).…”
Section: Genomic Characterization and In-silico Taxonomic Validation Of Sequenced Strainsmentioning
confidence: 99%
“…The increasing genomic representation of Vibrio sequences in public database enables a more comprehensive analysis and understanding of the evolutionary relationships among different species and strains (Osama et al, 2012, Jun et al, 2013, Gomez-gil et al, 2014, Gomez-Jimenez et al, 2014, Kondo et al, 2014, Yang et al, 2014, Castillo et al, 2015. The generation of high-quality draft genomes also allows the extraction of full-length house-keeping genes used for multilocus sequencing typing (MLST), precluding the laborious steps associated with amplification and sequencing of multiple PCR fragments (Osama et al, 2012, Joensen et al, 2014, Kavousi et al, 2016.…”
Section: Introductionmentioning
confidence: 99%